Coeloglossum viride var. bracteatum extract improves learning and memory of chemically-induced aging mice through upregulating neurotrophins BDNF and FGF2 and sequestering neuroinflammation. (June 2019) - Zhong, Si-Jia; Wang, Lin; Wu, Huan-Tong; Lan, Rongfeng; Qin, Xiao-Yan
Graphical abstract: Coeloglossum viride var. bracteatum extract (CE), from a traditional Tibetan medicine Zang wangla, improves learning and memory of aging mice through upregulating neurotrophins BDNF and FGF2 and sequestering neuroinflammation. Highlights: CE effectively improves learning and memory of aging mice. CE enhances the mRNA expression of BDNF and FGF2 in hippocampus of aging mice. CE is effective in remitting aging associated cognitive impairment. Abstract: CE exerted neuroprotective effects against a range of oxidative stress and amyloid toxicity in neurons. Here, we investigated the anti-aging effects of CE in chemically-induced aging mice established by consecutive administration of D -galactose combined with AlCl3 . Behavior analysis verified that CE significantly ameliorates learning and memory deficit of aging mice. CE treatment evoked the hippocampus expression of neurotrophins BDNF and FGF2, reactivated PI3K/Akt signaling pathway and rescued the decline of anti-apoptotic protein Bcl-2, but abolished the elevation of active Caspase-3. Meanwhile, the expression of inflammatory factors including TNF-α, IL-6, NOS2 and IL-1β was decreased. Collectively, we established the neuroprotective role of CE that ameliorates chemically-induced cognitive deficit through up regulation of BDNF and FGF2, reactivating the PI3K/Akt signaling pathway and sequestering neuroinflammation. Our work will assist in the development of functional food and medicine for clinical trials of anti-aging and dementia.